Scholarly communication's mess : can economic analysis help? - Budd, John M. (2021)
This paper constitutes a trial of a game- and decision-theory based approach that is intended to examine elements of the complexities of scholarly communication as an economic endeavor. Both individual and institutional kinds of games are analyzed in order to determine what factors would affect the real economic use of game and decision theories. There are interrelationships between the two kinds that add complexity to any possible application. Further, this analysis includes ideal and practical factors that affect real economic application. As is shown here, there are serious challenges to application of the theories, but also important indicators for the furtherance of individual and institutional interests by means of negotiation.